Where-Provenance for Bidirectional Editing in Spreadsheets - Williams, Jack; Gordon, Andy (VL/HCC 2021, 2021)
We explore the idea of adding bidirectionality to spreadsheet formulas, so that editing the output can directly affect the input. We introduce portals: a portal is a value paired with its where-provenance, that is, one or more links to its origin. When a portal is the result of a formula in a cell, that cell inherits the capability to edit the locations described by the provenance of the portal. The simplicity of portals makes them amenable to implementation in an existing spreadsheet system. We analyse the list of functions provided by a widely-used commercial spreadsheet system and find that many frequently used functions work with portals with no modification.
Pre-print. Full publication will be available from IEEE.